2016
DOI: 10.1093/infdis/jiw256
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Benefits of Routine Human Papillomavirus Vaccination for Adults in the Netherlands: A Mathematical Modeling Study

Abstract: Offering vaccination to adults, especially at cervical cancer screening visits (for women) and during STI consultations (for both sexes), would substantially reduce HPV incidence and would be an efficient policy option to improve HPV prevention and subsequently avert cervical and possibly male HPV-related cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…5 Epidemiological impact of two vaccination strategies on HPV16/18/31/33/45/52/58 related incidence of CIN3 over 100 years only vaccination programme [46]. Other European epidemiological-focused published models in Germany [47], in Italy [48], in the Netherlands [49], and in Finland [50] have shown the positive epidemiological impact of gender-neutral HPV 2-valent and/or 4-valent vaccination. Besides, several cost-effectiveness studies recently published in Europe reported findings on the epidemiological impact of switching from a 4-valent vaccination to a 9-valent vaccination programme in a gender-neutral context [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…5 Epidemiological impact of two vaccination strategies on HPV16/18/31/33/45/52/58 related incidence of CIN3 over 100 years only vaccination programme [46]. Other European epidemiological-focused published models in Germany [47], in Italy [48], in the Netherlands [49], and in Finland [50] have shown the positive epidemiological impact of gender-neutral HPV 2-valent and/or 4-valent vaccination. Besides, several cost-effectiveness studies recently published in Europe reported findings on the epidemiological impact of switching from a 4-valent vaccination to a 9-valent vaccination programme in a gender-neutral context [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…We used largely the same assumptions to model the impact of HPV vaccination as in our previous studies [7, 9]. Briefly, we modeled the current vaccination strategy and observed vaccination uptake in the Netherlands: i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For the adult vaccination strategies, we assumed an efficacy of 77.4% against both HPV-types for women older than 24 years [34]. For men older than 24 years, vaccine efficacy was assumed to be 64.5% for HPV-16 and 80.6% for HPV-18 [9, 34]. In the last strategy, where the vaccine is offered to both sexes during STI consultations, routine vaccination for boys is included as well.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations